Characterization of Natural and Alkaline-Oxidized Proanthocyanidins in Plant Extracts by Ultrahigh-Resolution UHPLC-MS/MS - Karonen, Maarit (Molecules, 2021)
In this study, we analyzed the proanthocyanidin (PA) composition of 55 plant extracts before and after alkaline oxidation by ultrahigh-resolution UHPLC-MS/MS. We characterized the natural PA structures in detail and studied the sophisticated changes in the modified PA structures and the typical patterns and models of reactions within different PA classes due to the oxidation. The natural PAs were A- and B-type PCs, PDs and PC/PD mixtures. In addition, we detected galloylated PAs. B-type PCs in different plant extracts were rather stable and showed no or minor modification due to the alkaline oxidation. For some samples, we detected the intramolecular reactions of PCs producing A-type ether linkages. A-type PCs were also rather stable with no or minor modification, but in some plants, the formation of additional ether linkages was detected. PAs containing PD units were more reactive. After alkaline oxidation, these PAs or their oxidation products were no longer detected by MS even though a different type and/or delayed PA hump was still detected by UV at 280 nm. Galloylated PAs were rather stable under alkaline oxidation if they were PC-based, but we detected the intramolecular conversion from B-type to A-type. Galloylated PDs were more reactive and reacted similarly to nongalloylated PDs.